Model Test of Jacked Pile Penetration Process Considering Influence of Pile Diameter - Wang, Yonghong; Sang, Songkui; Liu, Xueying; Huang, Yongfeng; Zhang, Mingyi; Miao, Dezi (Frontiers in Physics, 2021)
In order to investigate the influence of different diameters on pile end resistance, pile side resistance, pile axial force and pile force transmission law of jacked pile penetration, pre-buried sensitized micro-fiber grating sensor through pile body slotting, two pairs The pile-jacking process of static-pressing viscous foundation soil with different diameters of closed-tube model piles was successfully monitored. The test results show that the pile pressure, pile end resistance and pile side resistance of the two test piles increase linearly with the increase of pile depth. When the pile jacks, the final pressure of the test pile TP1 is higher than that of the test pile. TP2 is 31% higher, pile end resistance is 18% higher, and total side resistance is 57% higher. The results show that increasing the pile diameter can significantly increase the pile side resistance; under different penetration depths, the pile side resistance is from top to end. Continuously exerted, the axial force of the pile body decreases with the depth of the pile and the slope of the distribution curve of the axial force gradually decreases. At the maximum penetration depth, the axial force of the pile TP1 is 18% larger than that of the test pile TP2; As the depth increases, the unit side resistance at the same penetration depth gradually decreases, that is, the side resistance has a “degradation effect”; at the end of the pile jacking, the percentage of the pile end resistance to the pile force exceeds 50%, that is, the pile end resistance bears most of the load.